REINFORCEMENT PENDIDIKAN MULTIKULTURAL DI PONDOK PESANTREN NGALAH - M. Jamhuri; Saifulah; Muhammad Haidar Hadziq (Journal Multicultural of Islamic Education, 2023)
In the Ngalah Islamic Boarding School education, reinforcement is needed to achieve the goals of education. The focus of the research taken is 1) how is the verbal reinforcement of multicultural education on students at the Ngalah Islamic Boarding School?. 2) how is the non-verbal reinforcement of multicultural education for students at the Ngalah Islamic Boarding School?. The results showed that the verbal reinforcement of multicultural education at the Ngalah Islamic Boarding School was carried out in three ways. The first is through the reinforcement carried out by the caregiver at the recitation led by the nanny. Second, the reinforcement carried out by the Management or Ustadz during student activities. Third, through the work of Islamic Boarding Schools which contains about multiculturalism. While the non-verbal reinforcement of multicultural education is carried out in five ways, namely, first, through the naming of existing buildings in the Ngalah Islamic Boarding School area. Second, the design of buildings and objects there uses a typical Nusantara design. Third, through inter-religious meetings organized by the Ngalah Islamic Boarding School. The four clothes used by caregivers or administrators use typical Indonesian cultural clothing. Fifth, through symbols or cover images of books by Islamic boarding schools that use images of Nusantara culture.